If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 10 = -17 + -2x Reorder the terms: 10 + x = -17 + -2x Solving 10 + x = -17 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 10 + x + 2x = -17 + -2x + 2x Combine like terms: x + 2x = 3x 10 + 3x = -17 + -2x + 2x Combine like terms: -2x + 2x = 0 10 + 3x = -17 + 0 10 + 3x = -17 Add '-10' to each side of the equation. 10 + -10 + 3x = -17 + -10 Combine like terms: 10 + -10 = 0 0 + 3x = -17 + -10 3x = -17 + -10 Combine like terms: -17 + -10 = -27 3x = -27 Divide each side by '3'. x = -9 Simplifying x = -9
| 0=r^2-104.04 | | 6m-10=2m+6 | | 8x+7y=51 | | 8(4x+6)=-8x | | 8+5n=-(-8n-6)-4 | | 25s+40t= | | 9-7x=7x+37 | | 12/a=132/35 | | 3cosx+4=5cosx+5 | | 5cosx=-5sinx | | u/5=5.7 | | -6(x+4)=8(x-4) | | 2/11=4/t-1 | | 4/5x5/9 | | x+x(.1)=150000 | | 1x^2-8+6y^3+3y-12x=2 | | 2+3x=7x-22 | | 3/6h=12/72 | | 8(6n-6)=7-7n | | -4(-2x+5)=9x | | 4/7y-1/3=1/5 | | 785+86= | | (2x+5)=6x+15 | | -2(3x+2)=-14x-2 | | 6x+8=3x+2 | | -388=7(7r+1)-3 | | -14+17=-3(x+8) | | y=34-0.5x | | 2(m-3)+5=19 | | Sen(2x)-2*cosx=0 | | -8n+3=-5n-6 | | -6k+k^2=7 |